L-Histidine-Modified Silica from Rice Husk and Optimization of Adsorption Condition for Extractive Concentration of Pb(II) - Nurhajawarsi Nurhajawarsi; Mohamad Rafi; Utami Dyah Syafitri; Eti Rohaeti (The Journal of Pure and Applied Chemistry Research, 2018)
A new chelating agent, L-histidine-modified silica from rice husk (LHSRH), was prepared to increase the adsorption capacity and selectivity for Pb(II). LHSRH was synthesized by immobilizing L-histidine on silica from rice husk (RH) modified with 3-aminopropyltrimethoxysilane (APTMS). Silica from rice husk (SRH) was synthesized via precipitation process by adding hydrochloric acid solution to rice husk ash (RHA). The RHA was subsequently destructed with sodium hydroxide and heated to obtain sodium silicate (Na2SiO3). SRH was characterized by Fourier transform infrared spectroscopy and x-ray diffraction. The LHSRH was used further to adsorp Pb(II) metal ion. The pH range, amount of adsorbent, and adsorption time were optimized by response surface methodology. The optimum condition for the adsorption of Pb(II) was pH 5, an amount of adsorbent 0.1 g; and adsorption time 15 minutes. The adsorption capacity for Pb(II) ion was found to be 62.5 mg/g. The adsorption behavior of the matrix followed the Langmuir’s model.